Causes, trends and severity of musculoskeletal injuries in Ghana - Torgbenu, Eric Lawer (BMC Musculoskelet Disord, 2017)
BACKGROUND: Musculoskeletal [MSK] injuries are common causes of long-term pain and physical disability which affect many people worldwide. The economic and social impacts on the individual, society and national health systems are enormous making a matter of public health concern. Therefore, this study examined the causes and extent of MSK injuries in a referral hospital in Ghana. METHODS: A prospective study design with consecutive sampling method was used to recruit patients admitted at Trauma Unit as well as those receiving orthopaedic reviews at St. Joseph’s Orthopaedic Hospital over a ten-month period. A structured questionnaire, Visual Analogue Scale (VAS) and Abbreviated Injury Scale (AIS) were used to collect data which were analysed descriptively using SPSS version 20. RESULTS: A total of 269 MSK injury patients were identified - of these, 137 (50.9%) males with an average age of 38 years (SD = 19.88). Nearly half (49.1%) of the injuries sustained were fractures, and common causes were vehicular crash 113 (42.0%) and fall 68 (25.3%). Body parts affected most were the knee (19.62) and the mean levels of pain for all injuries were 6.04 ± 2.44 and 3.25 (±1.50) respectively. CONCLUSION: Ghana needs a healthy population to steer its development trajectory. Policy makers in Ghana should pay attention to both preventive as well as management of MSK injuries, or else, most of the country’s working class could live with lasting effects of injuries which may have significant impacts on the economy.